Cheated: The Psychoanalysis on a Transgender Person - Helena Lorentia (Institute of Research and Community Outreach - Petra Christian University, 2017)
This creative works tells a story about a husband who hides his true identity from his wife. He is actually a transgender person who has a desire to be a woman, but he represses his desire and tries to live as a man. I choose the transgender topic because there are a lot of transgender people around us who repress their true sexuality because of the society norms and beliefs. Therefore, my story wants to explore more on this topic with the help of the theory of defense mechanism by Freud to explain why and how the husband represses his sexuality, and to explain the effects caused by the repression. The story is presented through the drama and psychological thriller genre to suit the style of the creative work which focuses on the psychological state of the main characters and the complexity within them,